Repetitions in reserve is a reliable tool for prescribing resistance training load - Lovegrove, S.; Hughes, L. J.; Mansfield, S. K.; Read, P. J.; Price, P.; Patterson, S. D. (The Journal of Strength and Conditioning Research, 2022)
This study investigated the reliability of repetitions in reserve (RIR) as a method for prescribing resistance training load for the deadlift and bench press exercises. Fifteen novice trained men (age: 17.3 ± 0.9 years, height: 176.0 ± 8.8 cm, body mass: 71.3 ± 10.7 kg) were assessed for 1 repetition maximum (1RM) for deadlift (118.1 ± 27.3 kg) and bench press (58.2 ± 18.6 kg). Subsequently, they completed 3 identical sessions (one familiarization session and 2 testing sessions) comprising sets of 3, 5, and 8 repetitions. For each repetition scheme, the load was progressively increased in successive sets until subjects felt they reached 1-RIR at the end of the set. Test-retest reliability of load prescription between the 2 testing sessions was determined using intraclass correlation coefficient (ICC) and coefficient of variation (CV). A 2-way analysis of variance with repeated measures was used for each exercise to assess differences in the load corresponding to 1-RIR within each repetition scheme. All test-retest comparisons demonstrated a high level of reliability (deadlift: ICC = 0.95-0.99, CV = 2.7-5.7% and bench press: ICC = 0.97-0.99, CV = 3.8-6.2%). Although there were no differences between time points, there was a difference for load corresponding to 1-RIR across the 3 repetition schemes (deadlift: 88.2, 84.3, and 79.2% 1RM; bench press: 93.0, 87.3, and 79.6% 1RM for the 3-, 5-, and 8-repetition sets, respectively). These results suggest that RIR is a reliable tool for load prescription in a young novice population. Furthermore, the between-repetition scheme differences highlight that practitioners can effectively manipulate load and volume (repetitions in a set) throughout a training program to target specific resistance training adaptations.